Low-redshift Type Ia Supernova from the LSQ/LCO Collaboration. (26th March 2021) - Baltay, C.; Grossman, L.; Howard, R.; Rabinowitz, D.; Arcavi, I.; Barbour, N.; Burke, J.; Contreras, C.; Dilday, B.; Graham, M.; Hiramatsu, D.; Hossenzadeh, G.; et al.
Abstract: This paper is the data release of a new sample of 140 type Ia supernovae (SNe Ia) from the LaSilla-QUEST/Las Cumbres Observatory (LCO) collaboration. The discovery of the supernovae came from the LaSilla-QUEST variability survey, the ASASSN survey, as well as smaller low redshift supernova surveys. All of the supernovae in this sample were spectroscopically identified as SNe Ia using spectra from the PESSTO survey using the 3.5 m NTT telescope at LaSilla and spectra from the LCO 2 m Faulkes telescopes. The light-curves were obtained from a rapid cadence photometric follow up of the supernovae with the 9 LCO 1 m telescopes located at various observatories around the globe. Reference images of the host galaxies were taken approximately a year after the supernova have faded to allow precise galaxy background subtraction from the supernova magnitudes. The supernovae in this sample were discovered over a seven year period from 2012 October to 2019 June, and the last galaxy reference images were taken before 2020 June.